Foreign Borrowing and Export Promotion Policies. (IMF Working Papers; Working Paper ;, 1989)
This paper considers the problem of allocation of investment for a debtor country that faces a ceiling on the amount of foreign debt it can accumulate. It shows that it is optimal for the debtor country to create a more open economy by favoring investment in the export sector over investment in the import-competing sector. The reason is that a more open economy is more sensitive to trade sanctions and therefore more creditworthy in international markets. Because international creditworthiness is basically an externality, there is a role for policy to provide higher returns to export producing activities.